2017
DOI: 10.1103/physrevb.96.235127
|View full text |Cite
|
Sign up to set email alerts
|

Role of three-particle vertex within dual fermion calculations

Abstract: We investigate the influence of self-energy diagrams beyond the two-particle vertex level within dual fermion theory. Specifically, we calculate the local three-particle vertex and construct from it selected dual fermion self-energy corrections to dynamical mean field theory. For the two-dimensional Hubbard model, the thus obtained self-energy corrections are small in the parameter space where dual fermion corrections based on the two-particle vertex only are small. However, in other parts of the parameter spa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…This procedure does not allow us to calculate all components of the multiorbital vertex function, a limitation that was overcome by Gunacker et al, 2015 using worm sampling. Let us also note a first calculation of the local threeparticle vertex using CT-INT (Hafermann et al, 2009c), CT-AUX, and CT-HYB (Ribic et al, 2017a). Slices through this three-particle vertex show similar structures as the two-particle vertex shown above.…”
Section: Exact Diagonalizationmentioning
confidence: 72%
“…This procedure does not allow us to calculate all components of the multiorbital vertex function, a limitation that was overcome by Gunacker et al, 2015 using worm sampling. Let us also note a first calculation of the local threeparticle vertex using CT-INT (Hafermann et al, 2009c), CT-AUX, and CT-HYB (Ribic et al, 2017a). Slices through this three-particle vertex show similar structures as the two-particle vertex shown above.…”
Section: Exact Diagonalizationmentioning
confidence: 72%
“…DMFT calculations are performed with the continuous time auxiliary field quantum Monte Carlo method [43,44] with submatrix updates [45]. DF is accurate at high temperature [46] but uncontrolled in practice in the sense that adding systematic corrections, while possible in theory [47,48], is not feasible for the parameters studied here. A detailed assessment of the approximation errors of the susceptibility and the single-particle properties on the square lattice [49] showed that while dopingand interaction dependent scaling effects were present, the overall momentum dependence was accurate.…”
mentioning
confidence: 99%
“…Hence, we calculate at least selected threeparticle diagrams as an error estimate after convergence of the two-particle approach, in the same way as in Ref. 28.…”
Section: Recapitulation Of the Methodsmentioning
confidence: 99%